2008
DOI: 10.1002/gcc.20609
|View full text |Cite
|
Sign up to set email alerts
|

Multiple recurrent chromosomal breakpoints in mantle cell lymphoma revealed by a combination of molecular cytogenetic techniques

Abstract: Mantle cell lymphoma (MCL) is genetically characterized by 11q13 translocations leading to the overexpression of CCND1, and additional secondary genomic alterations that may be important in the progression of this disease. We have analyzed 22 MCL cases and 10 MCL cell lines using multicolor fluorescence in situ hybridization (M-FISH), FISH, and comparative genomic hybridization (CGH). The 19 cases with abnormal karyotype showed the t(11;14)(q13;q32) translocation and, additionally, 89% of cases showed both num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
(57 reference statements)
2
19
0
Order By: Relevance
“…1,2 In addition to this primary genetic alteration, MCL also has a relatively specific profile of secondary genetic aberrations that include frequent losses, gains and recurrent chromosomal breakpoints. [3][4][5][6][7] In spite of the constant overexpression of cyclin D1 in MCL, some studies reported tumors with similar morphological and phenotypic characteristics but lacking the t(11;14) translocation and cyclin D1 expression. 8 However, it was controversial whether the apparent lack of cyclin D1 was a real biological phenomenon or was due to technical limitations in its detection.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to this primary genetic alteration, MCL also has a relatively specific profile of secondary genetic aberrations that include frequent losses, gains and recurrent chromosomal breakpoints. [3][4][5][6][7] In spite of the constant overexpression of cyclin D1 in MCL, some studies reported tumors with similar morphological and phenotypic characteristics but lacking the t(11;14) translocation and cyclin D1 expression. 8 However, it was controversial whether the apparent lack of cyclin D1 was a real biological phenomenon or was due to technical limitations in its detection.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that such loss of regulatory regions in the 3ЈUTR of the human GFI1 gene might likewise contribute to human lymphomagenesis. The human GFI1 gene is carried in the chromosomal region 1p22 (58), a locus commonly affected in several cancers, including mantle cell lymphoma (60,61), mucosa-associated lymphoid tissue lymphoma (77), and neuroblastoma (46). Although there has been no direct correlation between translocations in this region and the effect on the GFI1 gene, our studies support the importance of this genomic region in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…In most MCLs and in a substantial fraction of multiple myelomas 11q13 translocations are observed. [77][78][79][80] In addition to these malignancies, also hairy cell leukemia and some cells in the proliferation centers of chronic lymphocytic leukemia as well as extremely rare DLBCL cases may express CCND1, the mechanism being unknown. 81 Like the t(14;18), the t(11;14) in MCL is mediated by RAG1/2, probably in combination with low levels of AICDA as well as other mechanisms.…”
Section: Ccnd1mentioning
confidence: 99%